Adult Emergence and Morphometrics of Chinese Citrus Fly, Bactrocera minax (Enderlein) (Diptera: Tephritidae) in Nepal - Regmi, Bhawana; Tiwari, Sundar; Srivastava, Arvind; Lamsal, Hom Nath; Pandit, Januka; Shrestha, Shruti; Pandit, Shailesh; Adhikari, Debraj (International Journal of Environment, 2023)
Chinese citrus fly, Bactrocera minax is a destructive and univoltine pest of citrus fruits. Geographical altitudinal gradients as well as prevailing climate affect the biology and ecology of insect. Hence, this study aimed to ascertain the effect of altitude on the adult emergence and morphological variations in various ecological settings of Ramechhap district of Nepal from February to June 2021 in citrus orchard. Six altitude ranges were selected in 50 m distance from 1200 to 1500 m above sea level (masl), ranging from 1201-1250 masl, 1251-1300 masl, 1301-1350 masl, 1351-1400 masl, 1401-1450 masl and 1451-1500 masl. The peak adult emergence periods were the 2nd, 3rd, 4th week of April in 1201-1250 masl, 1251-1300 masl, 1301-1350 masl, respectively, followed by 1st, 2nd and 3rd week of May in 1351-1400 masl, 1401-1450 masl, 1451-1500 masl, respectively. Morphometrics of Chinese citrus fly such as weight, length and width of pupa and adult were almost similar to the species collected in various altitudes. The average body length of male Chinese citrus fly adult was 11.58± 0.112 mm while female was 15.57± 0.076 mm. The average wingspan of male was 20.71± 0.285 mm while that of female was 23.14± 0.156 mm. The longevity of adult Chinese citrus fly species increased with increase in altitude. This information could be useful to design an appropriate management plan of Chinese citrus fly in various altitudinal gradients of Nepal.